A retrospective study of CD44 immunohistochemical expression in recurrent breast cancer / Gan Soon Ching - Gan , Soon Ching (2017)
Purpose: C044 has been identified as a marker of breast cancer stem cells, which are important in the development of cancer invasion, metastasis and recurrence. This study aimed to investigate the utility of CD44 expression by immunohistochemistry in differentiating recurrent/metastatic breast cancer from non-recurrent/non-metastatic primary breast cancer in a diagnostic histopathology service setting. Materials and Methods: 4f lm thick sections from 69 archival formalin-fixed, paraffin-embedded breast cancer tissue, comprising 31 recurrent/metastatic and 38 non-recurrent/non-metastatic cancers, diagnosed between the years 2007 and 2015 in the University of Malaya Medical Centre were immunostained with C044 antibody on an automated platform (VENTANA BenchMark Ultra GX). C044 expression was evaluated on scores of 0-3 for intensity (0 = no staining, 1 = faint signal, 2 = moderate, and 3 = intense staining) and extent of positivity (O =no, 1 = <30%, 2 = 30%-70%, and 3 = >70% positive tumour cells). A cumulative score (Sum) at or above 2 was considered positive. H&E slides of the cancers were also reviewed for histological grading according to the modified Scarff Bloom & Richardson system Demographic information (ethnicity and age) and status of ER, PR and HER2 expressions were obtained from the histopathology reports. A comparison was made of CD44 expression and clinicopathological parameters between recurrent and non-recurrent groups. Result: The groups of recurrent and non-recurrent cancers did not differ significantly in the clinicopathological profiles investigated. The main parameter that achieved a statistically significant difference {p<0.021) was HER2 overexpression which was more common in recurrent {26.9%} than non-recurrent {5. 7%) cancers. CD44 was expressed in almost similar percentage in both recurrent (77.4%) and non-recurrent {71.1%) cancers. Although recurrent cancers had a higher mean CD44 sum {3.7) than the non-recurrent group (mean sum=3), this difference was not statistically significant. Conclusion: CD44 testing by immunohistochemistry does not appear to be useful as an isolated predictive or prognostic marker for recurrence or metastasis. Larger scale studies with outcome data and basic studies on cancer pathogenetic pathways will be required to cast further light on whether CD44 could have clinical utility in cancer progression.